An Unknown Tenth-Century Martyrs’ Trope Collection - Minniti, Giulio (Scrineum, 2025)
On the blank space of the recto side of a folio in a ninth-century Frankish manuscript now Paris, BnF Lat. 2846, a mid-tenth-century scribe entered a set of troped mass chants — an introit, an offertory and a communio — to be used in Martyrs’ masses. Not much later to judge by the script, two more scribes added yet more annotated troped introits on the verso of the same folio. Of the five trope sets adjoined to the five chants, one is now completely erased and illegible, another is found in two older sources, but, as this article shows, three of the trope sets are present here about half a century earlier than in the previously known sources. The comparison of this early source of tropes against those edited in the Corpus Troporum series, combined with the paleographic and philological analysis of its contents, and the evaluation of its relationship with perishable and poorly understood trope libelli, reveals the importance of this previously unnoticed minitext for the early history of tropes.